Робота Чернігівської міської думи на початку I світової війни (за матеріалами преси) - Подвербний, А. (Сiверянський лiтопис, 2017)
У статті за матеріалами газети «Черниговская земская неделя» висвітлені особливості роботи Чернігівської міської думи у другій половині 1914 року, описані суспільні та соціально-економічні процеси, яким приділяла найбільше уваги тодішня міська влада у ході початку військових дій Першої світової війни. В статье по материалам газеты «Черниговская земская неделя» освещены особенности работы Черниговской городской думы во второй половине 1914 года, описаны общественные и социально-экономические процессы, которым уделялось с началом военных действий Первой мировой войны наибольшее внимание тогдашней городской властью. The peculiarities of work of Chernihiv city duma (council) in the second half of 1914 with the beginning of military actions of the First World War, based on the materials of the newspaper «Chernihovskaia zemskaia nedelia» (Chernihiv district council week), have been highlighted; public and social and economic processes, on which the most attention was given by the contemporary city authorities, have been described in the article.